The Influence of Service and Religiosity on Taxpayer Compliance with Tax Sanctions as a Moderating Variable in MSMEs in Singkawang City - Nanang, Nanang; Hamzani, Umiaty; Yantiana, Nella; Noviarty, Helisa; Rusmita, Sari (Sebatik, 2024)
This study aims to analyze the influence of tax services and religiosity on the tax compliance of MSMEs in Singkawang City, with tax sanctions as a moderating variable. Tax compliance is a critical concern for the government, particularly in increasing state revenue from taxes, especially from the MSME sector. This research adopts a quantitative approach using a survey method involving 96 MSME actors in Singkawang City who are registered as taxpayers. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS. The findings reveal that tax services and religiosity have a significant positive effect on taxpayer compliance, indicating that high-quality tax services and strong religiosity can encourage greater compliance. Additionally, tax sanctions significantly impact compliance, showing that strict sanctions can enhance taxpayer adherence. However, tax sanctions do not moderate the relationship between tax services or religiosity and taxpayer compliance. This study concludes that to improve tax compliance among MSMEs, tax authorities should focus on enhancing service quality and reinforcing moral education through religiosity. Meanwhile, tax sanctions remain essential as a control mechanism, even though they do not consistently strengthen the relationship between services, religiosity, and compliance.